1989
DOI: 10.1007/bf02661798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing steps on the contents of minor compounds and oxidation of soybean oil

Abstract: The processes of degumming, alkali refining, bleaching and deodorization removed 99.8% phospholipids, 90.7% iron, 100% chlorophyll, 97.3% free fatty acids and 31.8% tocopherols from crude soybean oil. The correlation coefficient between the removals of phosphorus and iron in soybean oil during processing was r = 0.99. The relative ratios of α‐, β ‐, γ‐ and δ‐tocopherols in crude oil, degummed oil, refined oil, bleached oil and deodorized soybean oil were almost constant, γ‐ and δ ‐tocopherols represented more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
140
2
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(158 citation statements)
references
References 15 publications
13
140
2
3
Order By: Relevance
“…McLaughlin and Weihrauch (28) reported that deodorization causes the greatest loss of tocopherols, while little or no tocopherol is destroyed during hydrogénation. More recently, Jung et al (29) showed that the most substantial loss during refining of soybean oil occurred at the deodorization stage, while degumming, neutralization and bleaching led to an average retention of 88%. This value is very close to the value found in this work.…”
Section: Resultsmentioning
confidence: 99%
“…McLaughlin and Weihrauch (28) reported that deodorization causes the greatest loss of tocopherols, while little or no tocopherol is destroyed during hydrogénation. More recently, Jung et al (29) showed that the most substantial loss during refining of soybean oil occurred at the deodorization stage, while degumming, neutralization and bleaching led to an average retention of 88%. This value is very close to the value found in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Sepiolite, represented by Si 12 Mg 8 O 30 (OH) 4 (H 2 O) 4 8H 2 O which belongs to the group of silicate, is widely used to remove undesired components from household and industrial wastewaters and in various industrial manufacturing processes, it has not been previously tested for the purification of edible oils [13]. The highly desirable tocopherols were reduced during soybean oil refining, and this removal reduces oxidative stability and nutritional value of the refined oil when compared with the crude oil [14]. Tocopherols are more volatile than the neutral triacylglycerides and can be removed with the high temperature and high vacuum of deodorization.…”
Section: Introductionmentioning
confidence: 99%
“…Of these various components, most attention is given to the tocopherols. Jung and coworkers (Jung et al, 1989) and Ferrari (Ferrari, 1996) have studied the tocopherol content at all stages of processing for all isomers in the finished oil. The tocopherol content decreases during each step of processing and may be markedly reduced during deodorization, as the tocopherols are volatile under these conditions.…”
Section: Soybean Oil Deodorizer Distillate Production and Characterizmentioning
confidence: 99%